2021
DOI: 10.1038/s41598-021-89068-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex mass spectrometry method for simultaneous quantification of urinary proteins related to respiratory health

Abstract: Respiratory health of children is a health priority. Club cell protein (CC16) is an interesting biomarker of lung diseases and adverse effects towards the airway epithelium integrity. Osteopontin (OPN) and nuclear factor-kappa B (NF-κB) also play a role in respiratory health. The use of urine as biomarker source is useful in studies involving children but necessitates proper adjustment for physiological confounders influencing the urinary excretion, potentially characterized with beta-2-microglobulin (β2M), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Indeed, from previous studies and based on our field study setup, we found that, for the monitoring of protein biomarkers, urine was found to be easily collected and stored. Using an MRM method, previously validated [ 19 ] and applied in a similar study [ 23 ], allowed the simultaneous quantification of U-CC16, a biomarker of lung injury, permeability and respiratory diseases, as well as U-β2M and U-RBP4, two potential adjusters for variations in diuresis and renal handling of urinary proteins. For the genotyping and epigenetic methylation biomarkers, previous studies confirmed that saliva is a good non-invasive source [ 57 , 58 , 59 ], with DNA of such high quality that it could be used as an alternative to blood DNA in epidemiological studies [ 48 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, from previous studies and based on our field study setup, we found that, for the monitoring of protein biomarkers, urine was found to be easily collected and stored. Using an MRM method, previously validated [ 19 ] and applied in a similar study [ 23 ], allowed the simultaneous quantification of U-CC16, a biomarker of lung injury, permeability and respiratory diseases, as well as U-β2M and U-RBP4, two potential adjusters for variations in diuresis and renal handling of urinary proteins. For the genotyping and epigenetic methylation biomarkers, previous studies confirmed that saliva is a good non-invasive source [ 57 , 58 , 59 ], with DNA of such high quality that it could be used as an alternative to blood DNA in epidemiological studies [ 48 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on our field study setup, we found that, for the monitoring of protein biomarkers, urine could be analyzed using a validated MRM method [ 19 ]. The use of only 500 µL of urine was more than sufficient for performing a trypsin digest and to deliver a qualitative protein sample for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations